Agricultural trend and economic growth in Malaysia: An analysis / Mohamad Idham Md Razak, Nor Azizah Mohammad Amin and Faridah Pardi - Md Razak, Mohamad Idham; Mohammad Amin, Nor Azizah; Pardi, Faridah (2012)
Generally, an increased in productivity is a key to a healthy and flourishing the economy. Consequently, the trend in productivity, economy wide, is one of the most closely watched of our common economic performance indicators. Hence agriculture, in particular, has been a very successful sector of the Malaysian economy in terms of productivity growth. Agricultural productivity growth has been an important source of Malaysian economic growth throughout the years, but the year after independent has seen an even faster growth in agricultural productivity. It generated approximately 39.3 percent to the economic growth. However, due to several factors in example productivity, marketing, technical, institutional and social problems, the contribution keep decline. This study describes the contribution of the agricultural production to the economic growth from the year 1977 2006 by using the secondary data. The study also discussed factors that have affected productivity trends by applying technical information about the econometric approaches to measures the relationship of each variable by using the unit root test, co integration test and causality test. The results showed there is no co integration between each independent variable and dependent variable except for rubber. This study helps to enhance the current research about the agricultural production and economic growth by providing more advanced econometrics information.